Brief review of proportionality relationships:
When two quantities
![a,b](https://tex.z-dn.net/?f=a%2Cb)
are
![\textbf{directly}](https://tex.z-dn.net/?f=%5Ctextbf%7Bdirectly%7D)
proportional, that means any change in
![a](https://tex.z-dn.net/?f=a)
manifests a
![\textbf{direct}](https://tex.z-dn.net/?f=%5Ctextbf%7Bdirect%7D)
change (think "in the same direction") in
![b](https://tex.z-dn.net/?f=b)
.
Silly example: "The more I eat, the fatter I get." Here the amount one eats is directly proportional to one's body weight.
This change isn't always one-for-one, so we introduce a constant
![k](https://tex.z-dn.net/?f=k)
to account for any scaling that occurs on either variables behalf. In general, though, we can write a directly proportional relationship as
![a=kb](https://tex.z-dn.net/?f=a%3Dkb)
.
Now, when
![a,b](https://tex.z-dn.net/?f=a%2Cb)
are
![\textbf{inversely}](https://tex.z-dn.net/?f=%5Ctextbf%7Binversely%7D)
proportional, then a change in
![a](https://tex.z-dn.net/?f=a)
manifests a change in
![b](https://tex.z-dn.net/?f=b)
in the
![\textbf{inverse}](https://tex.z-dn.net/?f=%5Ctextbf%7Binverse%7D)
(opposite) direction.
Silly example: "The more I eat, the less thin I get."
This time we write the relation as
![ab=k](https://tex.z-dn.net/?f=ab%3Dk)
.
To get back to your problem: To say that the rate of change of
![y(x)](https://tex.z-dn.net/?f=y%28x%29)
is inversely proportional to
![\sqrt y](https://tex.z-dn.net/?f=%5Csqrt%20y)
is to say that there is some constant
![k](https://tex.z-dn.net/?f=k)
such that
![\sqrt y\dfrac{\mathrm dy}{\mathrm dx}=k](https://tex.z-dn.net/?f=%5Csqrt%20y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3Dk)
This is a separable ODE:
![y^{1/2}\,\mathrm dy=k\,\mathrm dx](https://tex.z-dn.net/?f=y%5E%7B1%2F2%7D%5C%2C%5Cmathrm%20dy%3Dk%5C%2C%5Cmathrm%20dx)
![\displaystyle\int y^{1/2}\,\mathrm dy=\int k\,\mathrm dx](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%20y%5E%7B1%2F2%7D%5C%2C%5Cmathrm%20dy%3D%5Cint%20k%5C%2C%5Cmathrm%20dx)
![\dfrac23y^{3/2}+C_y=kx+C_x](https://tex.z-dn.net/?f=%5Cdfrac23y%5E%7B3%2F2%7D%2BC_y%3Dkx%2BC_x)
![\dfrac23y^{3/2}=kx+C](https://tex.z-dn.net/?f=%5Cdfrac23y%5E%7B3%2F2%7D%3Dkx%2BC)
![y^{3/2}=\dfrac{3k}2x+C](https://tex.z-dn.net/?f=y%5E%7B3%2F2%7D%3D%5Cdfrac%7B3k%7D2x%2BC)